Disseminated fatal Talaromyces (Penicillium) marneffei infection in a returning HIV-infected traveller - N. P. Govender; R. E. Magobo; M. du Plooy; C. Corcoran; T. G. Zulu (AOSIS, 2014)
We report a case of disseminated fatal Talaromyces (Penicillium) marneffei infection in an HIV-infected, antiretroviral treatment-experienced South African woman who had travelled to mainland China. The 37-year-old woman was admitted to a private hospital in fulminant septic shock and died within 12 h of admission. Intracellular yeast-like bodies were observed on the peripheral blood smear. A serum cryptococcal antigen test was negative. Blood cultures flagged positive after 2 days; on direct microscopy, yeast-like bodies were observed and a thermally dimorphic fungus, confirmed as T. marneffei, was cultured after 5 days. The clinical features of HIV-associated disseminated penicilliosis overlap with those of tuberculosis and endemic deep fungal infections. In the southern African context, where systemic opportunistic fungal infections such as cryptococcosis are more common among HIV-infected patients with a CD4+ count of <100 cells/µL, this infection is not likely to be considered in the differential diagnosis unless a travel history is obtained.